Therapeutic hypothermia reprograms nanocarrier protein corona via apolipoprotein C1 enrichment for precision cardiovascular therapy - Chenwen Li; Guanli Zhao; Yuantong Qi; Menglong Sun; Ling Zhong; Qinghua Yang; Kaiyao Hu; Juan Cheng; Yin Dou; Yingxue Hao; Jianxiang Zhang (Proceedings of the National Academy of Sciences, 2025)
Cardiovascular diseases (CVDs), the primary cause of global mortality, face persistent therapeutic challenges due to poor drug targeting and systemic side effects. While innovative nanotherapeutic approaches offer improved drug delivery through targeting and stimulus-responsive release mechanisms, clinical translation is limited by poor tissue specificity and manufacturing limitations. We present a universal therapeutic hypothermia (TH, i.e., 32 to 35 °C)-enhanced strategy that amplifies nanocarrier targeting across multiple CVD models. Both hard and soft nanocarriers showed 1.6- to 3-fold increased pathological tissue accumulation under TH versus normothermia, correlating with enhanced therapeutic efficacy in multiple murine models of CVDs, including heart failure, myocardial hypertrophy, ventricular fibrillation, ischemic stroke, atherosclerosis, and deep vein thrombosis. Mechanistically, TH induces temperature-dependent enrichment of apolipoproteins C1 (ApoC1) and C4 in the protein corona of nanoparticle surface, enabling receptor-mediated targeting through upregulated lipoprotein receptors in injured cardiovascular tissues. Notably, ApoC1-mediated targeting outperformed established cardiac-targeting peptides in directing nanoparticles to diseased hearts. The TH-driven approach and direct ApoC1 functionalization provide a straightforward, scalable, and cost-effective approach to enhance nanotherapy precision for CVD treatment, potentially addressing critical barriers in clinical translation.